Development Strategy for Green Waqf Accounting in Riau Using the Analytical Network Process - Wali Saputra (Indo Publishing, 2026)
This study aims to analyze the development strategy for green waqf accounting in Riau Province using the Analytical Network Process (ANP) method. Green waqf accounting is a reporting and governance approach that emphasizes economic, social, and environmental sustainability (triple bottom line). The adoption of this concept is essential to support the transformation of waqf institutions toward transparent, accountable, and environmentally responsible Islamic financial practices. This research employs a quantitative descriptive approach using ANP to determine strategic priorities based on the perceptions of experts and stakeholders, including the Indonesian Waqf Board (BWI), local government, academics, and nazhir (waqf managers). Data were collected through pairwise comparison questionnaires and analyzed using the Super Decisions software. The ANP model in this study consists of four main clusters: (1) institutional and regulatory framework, (2) human resources, (3) digital technology and information systems, and (4) community participation. The findings indicate that the institutional and regulatory aspect has the highest priority weight (0.35), followed by human resources (0.27), digital technology (0.21), and community participation (0.17). The key sub-criteria influencing these priorities include transparency of waqf financial reporting, local government support, and the managerial capacity of nazhir in managing productive waqf. Based on the supermatrix limit results, the priority strategies include: (1) developing a digital-based green waqf accounting system, (2) enhancing nazhir human resource capacity, (3) strengthening regional regulations on green waqf accounting, and (4) implementing community-based green waqf literacy campaigns. This study contributes to developing a sustainable waqf governance model at the regional level and provides a foundation for local governments and waqf institutions in designing network-based policy strategies. The practical implication of this research highlights the importance of multi-stakeholder collaboration and digital technology adoption to establish a transparent, adaptive, and competitive green waqf accounting ecosystem.